The Expenditure Behavior of the Economic Literates - Abdul Jalil, Norasibah; Yusof, Hamidah; Rambeli, Norimah; Samsudin, Norsamsinar; Zakariya, Zainizam (International Business Education Journal, 2015)
The main purpose of this study is to explore students’ expenditure behavior and their effectiveness in managing their budget. The respondents are comprised of local university students from Business and Economics disciplines, whom are considered as economically and financially literates.1 In order to meet the objectives, three analyses; the income, expenditure and saving analyses, are carried out. The effectiveness of budget management is identified through the saving level. All analyses employ descriptive tests. The results of the first analysis recorded an average income worth RM889.66, while the spending level is RM1077.12 per month. The difference between the average income and spending level is -RM187.46. This difference is the value of the saving level. The finding provides indication that the university students have inclination to overspend. We these findings we may conclude, in terms of behavior, students have high inclination to spend more than their level of income, and this type of behavior implies university students’ financial management is ineffective.